Reconstruction of a Dynamic Robot-Based Table Tennis Ball Launcher as a Training Aid for Forehand Stroke Accuracy - Alfondha, Wilbert Robert; Juditya, Silvy; Heryanto, Mamat (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2025)
Abstract: A robotic-based training aid for forehand strokes in table tennis that utilizes a smartphone as a control medium has not yet been found. This research aims to understand the process of reconstructing a dynamic robot-based table tennis ball launcher as a training aid for forehand stroke accuracy. This type of research uses the ADDIE development method (analyze, design, development, implementation, evaluation). The analysis phase identifies user needs and characteristics, the design phase creates a 3D prototype design, the development phase creates and tests the product, the implementation phase tests the product on UKM members, and the evaluation phase is conducted at each product development stage. The subjects in this study included 1 media expert, 1 material expert, and 21 members of the STKIP Pasundan Table Tennis UKM, with instruments used to measure product quality in the form of questionnaires and surveys. The results of this study indicate that the dynamic robot-based table tennis ball launcher is deemed very feasible (86.65%) with a validity value of (0.510) and a reliability value of (0.518).Therefore, it can be stated that this dynamic robot-based table tennis ball launcher is "very feasible" to be used as an alternative training medium. Consequently, this tool can be recommended for use in technical training processes to enhance focus.Keywords: Tool reconstruction, ball thrower, table tennis.